Organization of rRNA structural genes in the archaebacterium Thermoplasma acidophilum. - Tu, J (1982)
In the archaebacterium Thermoplasma acidophilum, each of the structural genes for 5S, 16S and 23S rRNA occur once per genome. In contrast to those of eubacteria and eukaryotes, they appear unlinked. The distance between the 16S and the 23S rDNA is at least 7.5 Kb, that between 23S and 5S rDNA at least 6 Kb and that between 16S and 5S rDNA at least 1.5 Kb. No linkage between those genes has been found by the analysis of recombinant plasmids carrying Bam HI and Hind III rDNA fragments as by hybridizing those plasmids to fragments of Thermoplasma DNA generated by 6 individual restriction endonucleases, recognizing hexanucleotide sequences.